THE EFFECT OF ESTROGEN RECEPTOR AGONISTS ON PANCREATICOBILIARY DUCT LIGATION INDUCED EXPERIMENTAL ACUTE PANCREATITIS - (:unkn) unknown (POLISH PHYSIOLOGICAL SOC, 2017)
The 17 beta-estradiol plays a role in physiology of pancreas and may protect it from inflammation. To examine the possible anti-inflammatory effects of 17 beta-estadiol in pancreaticobiliary duct ligated (PBDL) acute pancreatitis (AP) model, and the underlying mechanism that 17 beta-estradiol acts on, via evaluating the direct and the receptor related effects by using 17 beta-estradiol, ER-alpha and -beta agonists. In the study both sexes of rats (n = 88) were used. Animals were divided into two groups as PBDL and PBDL + ovariectomized. ER-alpha agonist propyl-pyrazole-triol (PPT; 1 mg/kg/day), ER-beta agonist diarylpropionitrile (DPN; 1 mg/kg/day) and 17 beta-estradiol (10 mg/kg/day) were administered to the groups for 3 days following AP induction. On the 3rd day, lung and pancreas tissues and serum samples were taken for malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO), superoxide dismutase (SOD) and interleukin (IL) assays, and histological analyses. In both tissues of male and female AP groups MPO, MDA, SOD levels were increased (P < 0.05 - 0.01) and GSH levels were decreased (P < 0.05). Pancreas and lung MDA and SOD levels were improved with all treatments in female, except lung MDA levels of PPT-treated ones, while lung MDA and SOD levels were improved by PPT and 17 beta-estradiol in females and via PPT in males (P < 0.05 - 0.001). The increased MPO levels were inhibited with PPT in male pancreas and female lung and with 17 beta-estradiol in female pancreas (P < 0.05). The increased proinflammatory ILs were declined by treatments (P < 0.05 - 0.001). 1713-estradiol and ER-alpha and -beta agonists reduced oxidative pancreatic and pulmonary damage. Estrogen and agonists might have protective role in AP.
Keywords: acute pancreatitis; estrogen receptors; pancreaticobiliary duct ligation; oxidative stress; inflammation; 17 beta-estradiol; proinflammatory cytokines; REMOTE ORGAN INJURY; BETA-CELL FAILURE; LUNG INJURY; NECROTIZING PANCREATITIS; OXIDATIVE STRESS; PROTECTIVE ROLE; RATS; INFLAMMATION; ALPHA; MODEL